Assessment of quality of life in transfusion dependent thalassemic children - need to address parents/care givers - Sathenahalli, Veeraraja B.; Murthy, G. R. Rajashekar; Gouda, Netra; Shivanna, Sanjay K. (International Journal of Contemporary Pediatrics, 2020)
Background: Thalassemia is an autosomal recessive congenital disease caused by the reduced or absent beta globin chain synthesis of hemoglobin tetramer. The degree of imbalance between alpha and non alpha globin chains determines the severity of clinical manifestations. The disabling nature of the disease and chronic therapy affects the normal life causing psychosocial burden. Overall patient’s life, such as education, free-time, physical activities, skills, capabilities, and family adjustment is affected. The effects of which often result in psychological, emotional and social compromise. Health-Related Quality of Life (HRQoL) measurement is a multidimensional concept that focuses on the impact of the disease and its treatment on the well being of an individual. Methods: A descriptive observational hospital based study was conducted over a period of 3 months. Transfusion dependency in thalassemic children aged between 5 years and 18 years was the inclusion criteria. Thalassemic children having debilitating illnesses unrelated to thalassemia were excluded. Quality of life was assessed using Pediatric Quality of Life Inventory (PedsQL™ 4.0)4. The tool assesses the quality of life in five domains: physical functioning (PF: 8 items), psychosocial functioning (sum of emotional, social and school functioning), emotional functioning (EF: 5 items), social functioning (SF: 5 items) and school functioning (SC: 5 items). Results: Total of 125 children were enrolled with a mean age of 9.4±4.6 years (age range 5-18 yrs). According to the PedsQL questionnaire, the quality of life was similarly assessed by both parents and children. The total mean QoL score of the parents was 72.36±11.47 and of the children was 77.63±14.17. Emotional, school and psycho-social function were significantly affected according to both child and parents without statistical significance. Conclusions: Thalassaemia patients and their parents require lifelong psychological support for prevention of mental health issues. By increasing the awareness and knowledge levels of the parents, we can help sick children in developing countries to get the best care locally and to thus improve HRQoL.